Type 4 congenital proximal radio-ulnar synostosis mimicking as malunited radial neck and deformed radial head with insidious onset extension block: a case report and results after excision - Arora, Chandan; Jagtap, Satyajeet; Jain, Prateek; Sakharkar, Nilesh (International Journal of Research in Orthopaedics, 2022)
Proximal radio ulnar synostosis is a rare entity presenting with restriction of supination and pronation. Among the various types, type 4 variety is even more-rare and its presentation, can pose a diagnostic challenge specially, if with history of trauma. Radiologically, it is usually overlooked as a malunited radial neck and therefore needs thorough evaluation. We presented a case of a 15-year-old male who complains of new onset extension block following trauma, with chronically restricted supination and pronation. History suggested the restriction in supination and pronation since birth, and the extension block occurring de novo. Radiographs and CT scan of the elbow revealed proximal radio-ulnar synostosis and anteriorly dislocated, mushroom-shaped radial head, misleading and mimicking like an old, neglected and malunited radial neck fracture with a deformed radial head. The family insisted to not address the restriction of supination pronation but, asked for solution to more disabling extension block. Thus, patient was managed with open procedure, involving radial head-neck excision and removal of malformed radial head. At 1-year follow-up, the child has a well-reduced and stable elbow joint with a functional range of flexion and extension movements with restricted supination and pronation. Type 4 congenital radio ulnar synostosis not only leads to conventionally known restriction of supination pronation but also give rise to extension block de novo as presented in this case. Excision of the deformed head and neck can treat the restriction in extension, however the synostosis will require various other augmented procedures.